PERAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH SERVANT LEADERSHIP TERHADAP KOMITMEN ORGANISASIONAL PEGAWAI BPKAD KABUPATEN GIANYAR - Tukad, I Wayan Gde Arya Bhyasama; Surya, Ida Bagus Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The background of this research is the existence of organizational commitment problems that occur in employees. The purpose of this study was to analyze the influence of servant leadership on organizational commitment with job satisfaction as a mediation for employees of the Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Gianyar. The sample used is as many as 130 people who are determined through probability sampling technique with simple random sampling, which is taken randomly. Data was collected through interviews and questionnaires. The analytical technique used is a path analysis, sobel test, and VAF (Variance Accounted For) test. The results of this study indicate that servant leadership has a positive and significant effect on organizational commitment. Job satisfaction has a positive and significant effect on organizational commitment. Servant leadership has a positive and significant effect on job satisfaction. Job satisfaction mediates the influence of servant leadership on organizational commitment. The implications of the results of this study are expected to provide an understanding that when wanting to increase organizational commitment, the organization should be able to improve servant leadership, job satisfaction to its employees .